1996
DOI: 10.1002/etc.5620150604
|View full text |Cite
|
Sign up to set email alerts
|

Development of procedures for identifying pesticide toxicity in ambient waters: Carbofuran, diazinon, chlorpyrifos

Abstract: The responses of carbofuran, diazinon, and chlorpyrifos to standard acute toxicity identification evaluation (TIE) procedures were characterized. The test species was Ceriodaphnia dubia. The TIE procedures included solid‐phase extraction, recovery in methanol eluates, hydrolysis under acid and base conditions, and retention in specific methanol/water fractions. In addition, the effect of the metabolic inhibitor, piperonyl butoxide, on the toxicity of each of the pesticides was determined. Diazinon degraded qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 13 publications
6
44
1
Order By: Relevance
“…The TIEs then became a routine follow-up to the detection of toxicity. The U.S. EPA protocols were modified to specifically address pesticide toxicity [12,13], metal toxicity [14], algal toxicity [15], and the toxicity associated with urban storm runoff [13].…”
Section: Methodsmentioning
confidence: 99%
“…The TIEs then became a routine follow-up to the detection of toxicity. The U.S. EPA protocols were modified to specifically address pesticide toxicity [12,13], metal toxicity [14], algal toxicity [15], and the toxicity associated with urban storm runoff [13].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies involving invertebrates have demonstrated that PBO is highly toxic, with reported LC 50 values for water fleas (Ceriodaphnia dubia) and amphipods (Hyalella azteca) of 330 lg/L and 530 lg/L, respectively (Ankley and Collyard, 1995;Baily et al, 1996). By comparison, studies involving fish have demonstrated that PBO is only moderately toxic to this taxon, with reported LC 50 values ranging from 3940 lg/L in sheepshead minnow (Cyprinodon variegatus) to 11,200 lg/L in rainbow trout (Salmo gairdneri) (Erickson et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Piperonyl butoxide either completely eliminated or significantly reduced toxicity in 12 of the 14 samples. In all cases, sufficient diazinon was present to account for the acute toxicity; the fact that PBO did not eliminate toxicity in all cases suggests that other toxicants were present, because 200 ppb PBO should eliminate acute toxicity at diazinon concentrations of at least 1,500 ng/L [19]. Note that these studies were carried out only on the full-strength sample, so it is not possible to determine the exact contribution of metabolically activated organophosphorus pesticides to toxicity in cases where the toxicity was not completely eliminated.…”
Section: Fig 4 Temporal Variation In Diazinon Concentrations In Arcadementioning
confidence: 93%
“…Chem. 19,2000 H.C. Bailey et al averaged at least twice as high as those in the industrial catchment (sump 111).…”
Section: Comparison Of Industrial and Residential Catchmentsmentioning
confidence: 99%
See 1 more Smart Citation